The Relationship between Completeness of Medical Resume Data and the Accuracy of Pulmonary Tuberculosis Coding at Sumber Waras Cirebon Hospital 3rd & 4th Quarter 2024 - Sidqi, Raissa Aulia; Haryanto, Yanto; Rahmawati, Fitria Dewi; Aryani, Bhakti (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2025)
The medical resume is an important summary of the entire patient care process that serves as the basis for diagnosis coding and insurance claims based on ICD-10. The accuracy and completeness of medical resumes greatly affect clinical management, financial claims, and evaluation of the quality of health services. Pulmonary tuberculosis is an infectious disease that requires accurate diagnosis and coding to ensure optimal treatment. Based on data from the West Java Provincial Health Office, Cirebon Regency has a high prevalence of TB cases. Preliminary studies at Sumber Waras Hospital showed that there was still incompleteness in the medical resume and inaccuracies in coding the diagnosis of pulmonary TB. The purpose of this study was to analyze the relationship between the completeness of medical resumes and the accuracy of pulmonary TB diagnosis coding. The research method used was quantitative correlation with a total sampling approach to 72 medical record documents of pulmonary TB patients. Data analysis was performed using the chi-square test. Of the 72 medical record files of the main diagnosis of tuberculosis, there were 48 (48.0%) complete medical resumes and 24 (24.0%) incomplete medical resumes, there were 48 (48.0%) accurate diagnosis codes and 24 (24.0%) inaccurate diagnosis codes, there were 14 (59.3%) incomplete medical record filling completeness with inaccurate diagnosis codes, and there were 38 (79.2%) complete medical resume filling completeness with accurate diagnosis codes.